Refugee Entrepreneurial Economies in Urban South Africa (African Human Mobility Review, 2021)
The case-study literature on refugees and asylum-seekers in South Africa isdominated by an overwhelming focus on the problems they face and theirmarginalised existence, reinforcing an image of victimhood, exploitation andvulnerability. In this paper, we seek to broaden the image of refugees and theireconomic impacts beyond a narrow focus on their marginal status andvulnerable position. They are viewed here as dynamic agents with skills andcapabilities who can play an integral role in transforming local settings andcontributing to economic development. This paper presents and discusses theresults of a survey of over 1,000 refugee informal business-owners in Cape Townand small-town Limpopo.